2015
DOI: 10.1080/10942912.2015.1079789
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil and Phenolic Compounds ofArtemisia herba-alba(Asso.): Composition, Antioxidant, Antiacetylcholinesterase, and Antibacterial Activities

Abstract: Total phenols, flavonoids, flavonols, and flavanols of the methanolic extract of the aerial part of Artemisia herba-alba were determined. The extract was analyzed by liquid chromatography with photodiode array coupled with electrospray ionisation mass spectrometry and allowed to identify of 10 phenolic compounds. Apigenin-6-C-glycosyl flavonoids and caffeoylquinic acids were identified. Chlorogenic acid and 1,4 dicaffeoylquinic acid being the major constituents. The essential oil obtained by hydrodistillation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 42 publications
(47 reference statements)
2
30
1
Order By: Relevance
“…The other samples had a high proportion of borneol and thujone [42]. Recently, we studied the essential oil of an A. ha sample from Kairouan (Central Tunisia, upper arid bioclimate) and we found β -thujone (41.9%) as the major compound [29]. In other countries like Jordan, oxygen-containing monoterpenes represent also the main compounds of the oil [43].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The other samples had a high proportion of borneol and thujone [42]. Recently, we studied the essential oil of an A. ha sample from Kairouan (Central Tunisia, upper arid bioclimate) and we found β -thujone (41.9%) as the major compound [29]. In other countries like Jordan, oxygen-containing monoterpenes represent also the main compounds of the oil [43].…”
Section: Discussionmentioning
confidence: 99%
“…An amount of 150 g of ground material of each species was hydrodistilled in 1 L of water during 3 hours in a clevenger type apparatus. The obtained oil was dried using anhydrous sodium sulphate, centrifuged, weighed, and then stored at 4°C until analyses [29]. The oil yield was calculated in terms of % of its dry weight.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Natural products obtained from dietary and non-dietary sources are an armamentarium of pharmacological agents that have the potential to make a difference in the way alternative therapies are used in disease prevention. Studies have reported the pharmacological significance and associated health benefits of a number of spices used in various ethnic cuisines and food cultures worldwide [42][43][44].Modern medicine has revolutionized treatment strategies in the current period. However, in the light of emerging drug resistance in the cases of antibiotics and anti-cancer drugs, associated ill effects, organ toxicities, and expensive commercial interests leading to inaccessibility, it is believed to be judicious to have alternative strategies, such as prophylactic interventions, for most diseases associated with poor lifestyles, including stressful conditions, such as diabetes and gout.…”
Section: Resultsmentioning
confidence: 98%